Kegagalan Supremasi Hukum dan Hukum sebagai Rekayasa Sosial dalam Tragedi Kanjuruhan - Putra, Lucky Syah; Khoirunnisa, Nina; Muthmainnah, Siti; Sunanulhuda; Harahap, Chisa Belinda (Gunung Djati Conference Series, 2025)
The Kanjuruhan tragedy, one of the most tragic incidents in Indonesia's football history, raises significant questions about the rule of law and justice in Indonesia. This research aims to analyze how the principle of the rule of law was applied in the handling of this incident through the perspective of law as a tool for social engineering. Using a qualitative descriptive method with literature studies, the study examines systemic gaps in law enforcement and offers solutions to strengthen justice and public trust in Indonesia's legal system. Findings indicate that the excessive use of force by security forces highlights the failure of law enforcement to protect human rights, exacerbating public distrust. The study concludes that the implementation of a responsive, transparent, and accountable legal approach is crucial to ensuring justice for victims and their families and to fostering societal change for a more humane approach to crowd control. Recommendations include legal reform and educational measures to promote a better legal culture and to prevent future tragedies.